Training suggestions for the downhill mountain bike racer - Rhyan, S. (Strength and Conditioning Journal, 2005)
The 3 training patterns listed in the article are used in a rotating method, with each one used 1 time during a training week. The heavy-lifting pattern develops maximal strength and motor neuron output. Using moderate resistance with a fast motion helps develop muscle power and power endurance at fast speeds. The combined training day uses super sets to arrange the workloads into exercise blocks from a heavy-slow to lighter-fast movement pattern to help build athletic performance. This requires the participant to change movement speeds, resistance levels, angle of motion, and general work patterns in a very short period of time. This rapid adjustment of training patterns follows the rule of specificity for downhill mountain bike racing and will improve the performance and safety of the DMBR